PRODUKSI ASETON-BUTANOL-ETANOL DARI FERMENTASI CURAH DAN KONTINU OLEH CLOSTRIDIUM ACETOBUTYLICUM DENGAN SUBSTRAT GLUKOSA - Christon, Jeffry
Biobutanol is a potential biofuel that could compete in quality with conventional fossil fuel. Sustainable biobutanol production is possible through ABE (Acetone, Butanol, and Ethanol) fermentation by Clostridium acetobutylicum. ABE fermentation is able to produce acetone, butanol, and ethanol in a weight ratio of 3:6:1. However, Clostridium bacteria growth is liable to butanol toxicity. Thus, continuous fermentation is usually applied to reduce the inhibitive property of butanol produced from ABE fermentation as butanol produced can exit the reactor, thereby preventing butanol accumulation in the reactor. In this research, batch fermentation is done with variation in initial glucose concentration of 30, 40, 50, and 60 g/L to determine the best initial glucose concentration as well as constructing a model for ABE fermentation kinetics. Continuous fermentation is achieved with initial glucose concentration of 20 g/L to compare which fermentation mode is more effective. Batch fermentation with initial glucose concentration of 40 g/L is proven to produce the best result in butanol yield and productivity with values of 0.13 g butanol/g glucose and 0.083 g/L/h consecutively. Highest growth rate of Clostridium acetobutylicum is observed in batch fermentation with a value of 0.14 h-1. Fermentation model constructed with the Monod inhibited equation is achieved with the model quality parameter, ????2 and SSE of 0.66 and 0.0165 consecutively. Continuous fermentation with dilution rate of 0.15 h-1 produces butanol with a yield of 0.23 g butanol/g glucose and productivity of 0.093 g/L/h, thus proving that continuous fermentation is better suited for ABE fermentation instead of batch fermentation.